ANALISIS PEMAHAMAN MAHASISWA PENDIDIKAN FISIKA UNIVERSITAS JEMBER PADA MATERI TEKNOLOGI RADIASI IONIZING DALAM PENGAWETAN BAHAN PANGAN - Ahmad Nor Hamidy; Sudarti Sudarti; Trapsilo Prihandono (JURNAL PEMBELAJARAN FISIKA, 2021)
Most Physics Education students do not know about ionizing radiation technology in food preservation. This study aims to determine and analyze the ability of physics education students at the University of Jember in understanding ionizing radiation technology in food preservation. The research method used is a questionnaire method to 50 physics education students at the University of Jember. The research variable is students' knowledge of ionizing radiation technology as food preservation. The data collection technique used is by giving 10 multiple choice questions to 50 students of Physics Education. The results of student answers will be analyzed and represented in the form of tables and pie charts.